ANALISIS INTERFERENSI GRAMATIKAL DALAM TEKS BIOGRAFI SISWA - Sari, Ayu Puspita Indah; Harahap, Midra Azrianti (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
This research is motivated by the use of language in students' biographical texts. The problem in this research is how the form of grammatical interference in Indonesian language in the biographical text of class X students of SMA Negeri 1 Palembang  and what factors are the causes of the grammatical interference of Indonesian in the biography of students. The results of this study indicate that the form of Indonesian grammatical interference in the biographical text of students in the level of morphology includes affixation, reduplication, and composition. In affixation, there is a form of interference with one word prefix, prefix 4 words, 1 word prefix, suffix + suffix 1 word, confix 4 words, confirm + suffix 1 word , confixing 1 word, confirming 1 word, clophyte 1 word, and clophyte in one word, while the reduplication and composition process is not found in the biographical text of the student. Factors that cause the occurrence of grammatical interference are the participant's bilingualism, the thinness of the recipient's language loyalty, and the practice of habits in the mother language.